Actividad Fitotóxica del Aceite Esencial de Frutos de Schinus molle L.: Evaluación de su Potencial como Bioherbicida - Loyola-Gonzales, Eddie (2025)
Background: The indiscriminate use of synthetic herbicides has raised serious environmental and health concerns, driving the search for natural alternatives. Essential oils (EOs), due to their richness in bioactive terpenes, emerge as promising candidates for weed control. Schinus molle L., commonly known as “molle” or “Peruvian pepper tree,” produces an EO rich in monoterpenes whose phytotoxic potential remains scarcely explored in the literature. Materials and Methods: The EO from S. molle fruits was obtained by steam distillation and chemically characterized by gas chromatography coupled to mass spectrometry (GC-MS). Phytotoxicity was evaluated through seed germination bioassays using Lactuca sativa and root growth tests with Allium cepa bulbs, at concentrations of 0.1%, 0.5%, and 1.0%. Glyphosate (2%) and dimethyl sulfoxide (DMSO 0.1%) were used as controls. Results: GC-MS analysis identified 21 compounds, with α-phellandrene (28.63%), β-phellandrene (8.69%), and sabinene (6.74%) as the major constituents. The bioassays showed a significant concentration-dependent inhibition. At 1.0% EO, L. sativa germination decreased by 74.3% (p < 0.001), while A. cepa root growth was reduced by 65.2% (p < 0.001). Furthermore, the root/shoot ratio in L. sativa seedlings significantly decreased, indicating a greater impact on water and nutrient uptake during the early stages of development. Conclusion: The EO from S. molle fruits exhibited significant phytotoxic activity, supporting its potential as a natural bioherbicide. Although its effect was lower than that of glyphosate, the findings justify further research on its physiological and molecular mechanisms of action, as well as ecological and agronomic evaluations under field conditions.